Forms that Inform - O’Connell, R.; Poljak, A.; Powsner, S. (Methods of Information in Medicine, 2004)
Objectives: Sound medical decisions are easier for clinicians who have essential patient data in the right place at the right time. Our goal was to develop a usable form to guide clinical decisions and then test it using actual cases.Methods: The authors designed a form to represent data from patients with chest pain; it was revised several times. We incorporated opinions from clinician-users as well as evidence from the literature to improve usability. To test the design, we filled out forms with actual patient data derived from Emergency Department charts of patients who presented with chest pain. We then validated the design by having house officer reviewers make the decision to admit, observe in the ER for one day, or discharge subjects based entirely on a one-page form.Results: Thirty-three house officers reviewed our initial design and made suggestions. Our literature search yielded a number of factors discriminating ischemic from non-ischemic chest pain. Sixteen factors were included on a finalized form in the rank order assigned by reviewing physicians. Over 4 days, data from 29 subjects were used to fill out copies of the form. Based purely on the completed forms, house officers made decisions to admit, discharge, or observe all 29 subjects in less than 30 minutes.Conclusions: Forms have traditionally been employed to record and organize data. Here we show how principles of usability engineering can be used to create a form to meet the needs of users and even encourage evidence-based practice.
Keywords: Chest pain; hospital information systems; medical informatics; human engineering; evidence-based medicine